Slavic Length Again - Kapović, Mate (Array, 2005)
In this paper, the author explains some of the details of the development of Slavic length while comparing his own theory with the theory of Frederik Kortlandt. The author tries to prove the advantages of his own theory and shows some of the apparent shortcomings of the other approach which is found inadequate in describing the language material. In the article, the following problems are discussed (among others): the shortening of the final length, the reflection of the old acute and short neo-acute in Czech, the accentuation of the a. p. b definite adjectives, the problem of pretonic and posttonic length in South and West Slavic etc.